Blood MALT1 deficiency is common and relates to unfavorable induction therapy response and survival profile in acute myeloid leukemia patients - Haili Geng; Yiting Wang; Shaoyuan Wang (Hematology, 2022)
Background Mucosa-associated lymphoid tissue lymphoma translocation protein 1 (MALT1) regulates T helper/regulatory T cell balance, autoimmunity development, and leukemia pathogenesis. As a result, this study aimed to investigate the clinical role of MALT1 in patients with acute myeloid leukemia (AML).Methods MALT1 expressions were measured in peripheral blood mononuclear cell (PBMC) from 90 newly diagnosed AML patients before and after induction treatment using RT-qPCR. Moreover, MALT1 expressions were also determined in 50 disease controls (DCs) and 50 healthy controls (HCs).Results MALT1 expression was reduced in AML patients compared to HCs and DCs (both adjusted P < .001). Lower MALT1 expression was related to white blood cells >10×109/L (P = .037) and poor risk stratification (P = .020) in AML patients. MALT1 expression was elevated during induction treatment not only in total AML patients (P < .001), but also in subgroups of patients achieving complete remission (CR) (P < .001) and in those not achieving CR (P = .001). Furthermore, MALT1 expressions before induction treatment (P = .042) and after induction treatment (P < .001) were both increased in AML patients with CR compared to those with non-CR. Interestingly, both pre- and post-treatment MALT1 low (vs. high) were related to shorter accumulating event-free survival (EFS), which was also associated with a reduced accumulating overall survival (OS) (all P < .05). Furthermore, MALT1 increment during induction treatment < 50% was related to unsatisfied accumulating EFS (P = .001) and OS (P = .007).Conclusion PBMC MALT1 deficiency is common and relates to unfavorable induction therapy response and survival profile in AML patients.